Data Lake concept in the environment of an international organization - Rakhmanova, Malika (2020)
This master thesis aims to tackle the terms used in aviation, Data Lake and its evaluation and usage for the company optimization, improvements of key business processes and becoming a data-driven organization. First, it introduces of the concept of Data Lake, it’s components and functionalities. Second, it verifies the possibilities of using Data Lake in an enterprise in aviation industry as well as the concept and characteristics of data in aviation supply chain. Finally, it intends to provide an overview of the current ways of dealing with data in GE Aviation, for author to be able to examine and analyze them and due to that to envision possibilities of strategic development. The conclusion is based on the given analysis of GE Aviation specifics, data model and evaluation of current Aviation Data Lake.